2016
DOI: 10.1016/j.nrleng.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Guillain-Barré syndrome in a neurological Intensive Care Unit

Abstract: Introduction: Guillain-Barré syndrome, an acute polyradiculoneuropathy that presents with weakness and areflexia, is the most common cause of acute flaccid paralysis. In certain patients, respiratory failure is secondary to this disorder, eventually causing patients to require mechanical ventilation and experience additional complications due to diminished respiratory support and related mobility limitations. Prognoses for most of these cases are positive; treatment consists of basic support combined with plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
11
0
6
Order By: Relevance
“…1). Table 1 summarizes the main characteristics of all studies [14,16,25,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Search Resultsmentioning
confidence: 99%
“…1). Table 1 summarizes the main characteristics of all studies [14,16,25,[31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Search Resultsmentioning
confidence: 99%
“…Recently published comparative and noncomparative studies of GBS outcomes after treatment with TPE and/or IVIG have consisted primarily of case reports or case series from single institutions in developing countries, at which the choice between TPE and IVIG is largely dependent on economic considerations . Given the established equivalence between TPE and IVIG as effective treatments for GBS, it is important to evaluate patient‐ and hospital‐level characteristics that may affect treatment selection.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported by other Colombian studies completed in 2005, our results showed a predominance of the demyelinating form (AIDP) (70%) . Only one study in an intensive care unit (ICU) reported a higher prevalence of the axonal form (AMAN) . This may be explained by a greater need of ventilatory support among patients with AMAN .…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Only one study in an intensive care unit (ICU) reported a higher prevalence of the axonal form (AMAN). 16 This may be explained by a greater need of ventilatory support among patients with AMAN. 17 It has been documented that AMAN is more common in Japan, China, and some countries in Central and South America.…”
Section: Electrophysiology Featuresmentioning
confidence: 99%